A homozygous mutation in the integrin alpha6 gene in junctional epidermolysis bullosa with pyloric atresia. - Ruzzi, L (1997)
The alpha6 integrin subunit participates in the formation of both alpha6beta1 and alpha6beta4 laminin receptors, which have been reported to play an important role in cell adhesion and migration and in morphogenesis. In squamous epithelia, the alpha6beta4 heterodimer is the crucial component for the assembly and stability of hemidesmosomes. These anchoring structures are ultrastructurally abnormal in patients affected with junctional epidermolysis bullosa with pyloric atresia (PA-JEB), a recessively inherited blistering disease of skin and mucosae characterized by an altered immunoreactivity with antibodies specific to integrin alpha6beta4. In this report, we describe the first mutation in the alpha6 integrin gene in a PA-JEB patient presenting with generalized skin blistering, aplasia cutis, and defective expression of integrin alpha6beta4. The mutation (791delC) is a homozygous deletion of a single base (C) leading to a frameshift and a premature termination codon that results in a complete absence of alpha6 polypeptide. We also describe the DNA-based prenatal exclusion of the disease in this family at risk for recurrence of PA-JEB. Our results demonstrate that, despite the widespread distribution of the alpha6 integrin subunit, lack of expression of the alpha6 integrin chain is compatible with fetal development, and results in a phenotype indistinguishable from that caused by mutations in the beta4 chain, which is expressed in a more limited number of tissues.